2004
DOI: 10.1084/jem.20040298
|View full text |Cite
|
Sign up to set email alerts
|

Role for CD4+ CD25+ Regulatory T Cells in Reactivation of Persistent Leishmaniasis and Control of Concomitant Immunity

Abstract: Reactivation of dormant infections causes an immense burden of morbidity and mortality in the world at large. Reactivation can occur as a result of immunosuppression, environmental insult, or aging; however, the cause of reactivation of such infections is often not clear. We have previously shown that persistence of the parasite Leishmania major is controlled by endogenous CD4+ CD25+ regulatory T (T reg) cells. In this report, we show that despite efficient parasite clearance at secondary sites of infection, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
254
4
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 264 publications
(279 citation statements)
references
References 51 publications
(64 reference statements)
19
254
4
2
Order By: Relevance
“…Moreover, it is supposed that the frequent boosters provoked by endogenous parasites that may persist in lymphoid tissues (Barral et al 1995) or scars (Schubach et al 1998) as well as exogenous re-infections allow the establishment of a persistent pool of circulating experienced T-cells. This is in accordance with the idea that maintenance of T-cell mediated immunity requires the presence of an antigen (Kündig et al 1996, Mendez et al 2004, although it has been recently shown that a pool of memory T-cell can persist in the absence of antigen stimulation .…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, it is supposed that the frequent boosters provoked by endogenous parasites that may persist in lymphoid tissues (Barral et al 1995) or scars (Schubach et al 1998) as well as exogenous re-infections allow the establishment of a persistent pool of circulating experienced T-cells. This is in accordance with the idea that maintenance of T-cell mediated immunity requires the presence of an antigen (Kündig et al 1996, Mendez et al 2004, although it has been recently shown that a pool of memory T-cell can persist in the absence of antigen stimulation .…”
Section: Discussionsupporting
confidence: 69%
“…To date it is not clear whether, compared with the depleted population, the reappearing Treg have the full spectrum of the T-cell receptor repertoire and whether the GFP À DTR À Foxp3 1 Treg are fully functional. Unlike protozoan infections, where Treg were shown to play a beneficial and essential role for the survival of the parasite [13,14], we found that the interference with Treg activity had no influence on the worm burden. The removal of Foxp3 1 cells did not interfere with worm development and fecundity and did not lead to an early expulsion of adult worms.…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies investigated the role of Treg in infections with helminths or other parasites and yielded in diverging conclusions (reviewed in [1] and [13]). There is evidence that certain parasites depend on Treg action for their persistence [14][15][16][17]. Other species profit more indirectly from Treg circuits, which control infectioninduced pathology [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CD4 + CD25 + regulatory T cells may play important role in leishmaniasis [32] and seem to be stimulated by sand fly saliva [33,34]. In the present report, the marked production of pro-inflammatory cytokines such as IFN-c by normal volunteer's PBMC after SGS stimulation in vitro suggests that the T cells display an effector phenotype.…”
Section: Discussionsupporting
confidence: 42%